Linearly convex domains with singularities on the boundary - Mel’nik, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We present a topological classification of linearly convex domains with almost smooth boundary whose singularities lie in a hyperplane. We investigate sets with linearly convex boundary and the closures of linearly convex domains.